PEMODELAN DAN SIMULASI PROSES PENGERINGAN CHIPS MOCAF - Ariwibowo, Didik; Yohana, Eflita; Yulianto, M. Endy; Paramitha, Vita; Arifan, Fahmi (METANA, 2012)
This study was to propose the use of a simple heat and mass transfer based model to predict the evolutions of the moisture content and temperature of cassava chip undergoing superheated steam drying (SSD). Cassava chip has been chosen as the product to be simulated because of its various uses in the food especially as modified cassava flour (mocaf). Recently, superheated steam drying (SSD) has received much attention as an alternative drying technique for heat-sensitive biomaterials. There are a very limited number of works that report attempts to model this drying process, although there are a number of works that report studies of this drying technique experimentally. The results showed that the drying of the product is affected by the drying steam temperature and the product characteristics. The model was found to be able to predict the heat and mass transfer behavior. Keywords: Cassava chip, mocaf, superheated steam drying